Ireland : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2004)
The Selected Issues paper analyzes how fast Ireland will grow in the future. The approach of this paper is to consider the catch-up in labor utilization productivity and use independent demographic projections and other considerations to make reasonable assumptions about labor productivity and utilization growth in the future. It uses a simple growth-accounting framework, and discusses the trends in labor utilization and productivity per hour in the past. The paper also describes the spectacular boom of the Irish housing market and its key drivers from an international perspective.